Tantangan dalam Menghidupi Perkawinan Katolik di Tengah Perubahan Sosial dan Budaya - Yohanes Wilson B. Lena Meo; Alfridus Yorianto Sasi (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
This study provides an overview of some of the challenges faced in Catholic marriages. Some challenges related to marriage are issues that need serious attention from the church as one of the observers of marriage. How is the role of the church in living the spirit of love and solidarity in family life. The purpose of this study is to determine the complex problems that occur due to changes in the order of life from the influence of socio-cultural changes and to determine the response and role of the church in overcoming these life problems. The method used in this study is qualitative descriptive with a case study approach. The research data are in the form of interviews with several married couples as Catholic families. The findings in this study indicate that there are several problems that arise in married couples due to social and cultural changes, namely, economic problems, communication, technological advances, and long-distance relationships.